Sex steroid-induced DNA methylation changes and inflammation response in prostate cancer. (October 2016) - Wang, Songping; Clarke, Pamela A.G.; Davis, Roderick; Mumuni, Salma; Kwabi-Addo, Bernard
Highlights: Methylation of autoimmune and cytokine genes are influenced by steroid hormones. Observed inverse correlation between DNA methylation and cytokine gene expression. Pharmacological modification caused reversal in cytokine gene expression. Abstract: Background: Sex steroid hormones have been reported to induce inflammation causing dysregulation of cytokines in prostate cancer cells. However, the underlying epigenetic mechanism has not well been studied. The objective of this study was to evaluate the effect of sex steroid hormones on epigenetic DNA methylation changes in prostate cancer cells using a signature PCR methylation array panel that correspond to 96 genes with biological function in the human inflammatory and autoimmune signals in prostate cancer. Of the 96-gene panel, 32 genes showed at least 10% differentially methylation level in response to hormonal treatment when compared to untreated cells. Genes that were hypomethylated included CXCL 12, CXCL 5, CCL 25, IL1F 8, IL 13 RAI, STAT5 A, CXCR 4 and TLR 5; and genes that were hypermethylated included ELA 2, TOLLIP, LAG 3, CD 276 and MALT 1. Quantitative RT-PCR analysis of select genes represented in a cytokine expression array panel showed inverse association between DNA methylation and gene expression for TOLLIP, CXCL5, CCL18 and IL5 genes and treatment of prostate cancer cells with 5′-aza-2′-deoxycytidine with or without trichostatin A induced up-regulation of TOLLIP expression. Further analysis of relative gene expression of matched prostate cancer tissues when compared to benign tissues from individual patients with prostate cancer showed increased and significant expression for CCL18 (2.6-fold; p < 0.001), a modest yet significant increase in IL5 expression (1.17-fold; p = 0.015), and a modest increase in CXCL5 expression (1.4-fold; p = 0.25). In conclusion, our studies demonstrate that sex steroid hormones can induce aberrant gene expression via differential methylation changes in prostate carcinogenesis.